2022
DOI: 10.1002/adfm.202202087
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Insights of Stable, Monodispersed CsPbI3−xBrx (x = 0, 1, 2, 3) Nanocrystals Synthesized by Modified Ligand Cell

Abstract: Synthesis of monodispersed, stable halide, and mixed halide perovskite nanocrystals by hot‐injection approach is still challenging due to the fast reaction kinetics and unrevealed ligand chemistry. The atomic scale imaging of perovskite nanocrystals using transmission electron microscopy (TEM) is also challenging because of their structural degradation due to high electron dose and soft nature of perovskites. Here, a novel technique is proposed to synthesize pure cubic phase, monodispersed, stable CsPbX3 (X = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…It is well known that the transformation from Cs 4 PbI 6 !CsPbI 3 is feasible in the presence of a suitable ligand. [19,40] Hence, the addition of DSH to the aged sample eventually led to the revival of the thermodynamically stable cubic phase transformed from the trigonal Cs-rich Cs 4 PbI 6 .…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that the transformation from Cs 4 PbI 6 !CsPbI 3 is feasible in the presence of a suitable ligand. [19,40] Hence, the addition of DSH to the aged sample eventually led to the revival of the thermodynamically stable cubic phase transformed from the trigonal Cs-rich Cs 4 PbI 6 .…”
Section: Methodsmentioning
confidence: 99%
“…High-resolution transmission electron microscopy (HRTEM) images demonstrate that Ti 3 C 2 T x nanosheets retain the hexagonal crystal structure of the parent Ti 2 AlC phase (the insert of Figure 2k). The crystal plane spacing of 0.21 and 0.26 nm are corresponding to the (220) crystal plane of CsPbBr 3 [27] and (100) crystal plane of Ti 3 C 2 T x [28] (Figure 2l). The white interface implies the formation of Ti 3 C 2 T x -CsPbBr 3 heterojunction.…”
Section: Preparation and Characterization Of Pvdf/cspbbr 3 /Ti 3 C 2 ...mentioning
confidence: 99%
“…Mixing a small fraction of stable Cs + with the FA or MA-based perovskite successfully suppressed the formation of the optically inactive δ-phase by adjusting the GTF factor. 72 Park et al demonstrated that when 10% of FA + was replaced by Cs + in FAPbI 3 the water stability was improved and photodegradation under constant UV illumination was minimized. 73 Under continuous UV illumination (intensity = ∼100 mW cm −2 ) for 19 h, the FAPbI 3 film showed 86% degradation, but the FA 0.9 Cs 0.1 PbI 3 film showed 65% degradation.…”
Section: Stabilization Of Pencsmentioning
confidence: 99%